The Effect of Make A Match Cooperative Learning Model on Mathematics Learning Result and Interest at SMAN 1 Maron - Fattah, Gilang Fathurrohman; Sulaiman, Mahfudz; Qomariyah, Siti Nur; Sivakumar, Damonthara (Prodi Tadris Matematika Fakultas Tadris Umum, 2025)
This study aims to assess the effect of cooperative learning model Make a Match cooperative learning model on students' math learning outcomes and their interest in the subject at SMAN 1 Maron. the subject at SMAN 1 Maron. The participants of this study consisted of 72 students from two classes at SMAN 1 Maron. This research used quantitative method along with quasi-experimental design. Data analysis was conducted using N-Gain test, and normality assessment using the Shapiro-Wilk test revealing the value of Asymp. Sig. (2-tailed) for both classes were greater than 0.05, indicating a normal distribution. The results of the N-Gain test on the experimental group recorded at 48.96, placing it in the effective category. Findings from the Paired Sample T-Test comparing the pretest and posttest scores on the experimental group showed an Asymp. Sig. (2-tailed) of 0.00, which is less than 0.05, indicating a significant impact on outcomes and interest in math math learning. The results show that applying the Make a Match cooperative learning model in the experimental group positively affected students' mathematics learning outcomes and their interest in the subject.